KARAKTER MORFOMETRIK DAN MERISTIK IKAN KUNIRAN (Upeneus vittatus) DARI PLAWANGAN TIMUR SEGARA ANAKAN, CILACAP - Listyani, Mei; Putri, Adinda Kurnia (Universitas Gajah Putih, 2025)
The kuniran fish (Upeneus vittatus ) is a demersal fish. This species is able to grow up to 25 cm and inhabits sandy beaches with a depth of up to 100 meters. This study aims to describe the meristic and morphometric characters of Upeneus vittatus fish found in East Plawangan Segara Anakan, Cilacap. Sampling was conducted on June 24, July 23, and August 19, 2023 using a rampus net with a length of 36.576 m and a width of 6.4008 m. The results showed that Upeneus vitatus was found in the East Plawangan of Segara Anakan, Cilacap. The results showed that Upeneus vittatus had a total length range between 10.559 cm - 17.221 cm and an average of 5.686 cm ± 1.758 cm, while the meristic characters found have 7-8 SD 1, 6-13 SDL2 and 1-2 SDK 2, 3-15 SP, SVL 7-19, SVK 9-16, SAL 6-7, SAK 2, SC 21-27 , 36-38 SLL, 2-3 SALL, 6-7 SBLL, 11-12 SBAC. There were no significant differences in meristic and morphometric characters among the thirteen Upeneus vittatus fish found in East Plawangan, Segara Anakan.